2017
DOI: 10.1007/s12664-016-0720-6
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular liver biopsy in severe alcoholic hepatitis

Abstract: Cirrhosis is found in one third of patients with severe alcoholic hepatitis. This may alter our approach to management of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Thirty-one articles were excluded due to various reasons (Figure 1 ). Finally, 18 studies 9 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 were included in the systematic review. Three studies 26 27 28 did not provide data on the precision of clinical criteria for AH, leaving 15 studies for the quantitative meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one articles were excluded due to various reasons (Figure 1 ). Finally, 18 studies 9 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 were included in the systematic review. Three studies 26 27 28 did not provide data on the precision of clinical criteria for AH, leaving 15 studies for the quantitative meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of 18 studies, 9 were retrospective, 14 16 17 20 23 24 26 27 28 and 9 were prospective studies. 9 12 13 15 18 19 21 22 25 Of 15 studies included in the meta-analysis, 4 studies used NIAAA criteria, 17 20 22 25 4 used Classical criteria, 16 19 23 24 6 used European Association for Study of Liver 2012 criteria, 9 12 13 14 15 18 while 1 study did not report as to which criteria were used. 21 Eight studies 13 14 15 16 17 22 23 24 included patients with severe AH as defined by a discriminant function (DF ≥ 32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the majority of AH patients have underlying cirrhosis, although the prevalence rates have varied from 30-100% in different series. 5,6,52…”
Section: Liver Biopsy: Technique and Findingsmentioning
confidence: 99%
“…The literature is conflicting regarding the role of liver biopsy for diagnosis of AH 37,40,43,[52][53][54][55] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%